Nonhuman Animals and Decorative Modernism in Djuna Barnes and Mina Loy. Issue 1 (2nd January 2021) - Goody, Alex
Abstract: With a focus on their depiction of the use of nonhuman animal materials this article examines how Barnes and Loy's modernism specifically negotiates and disrupts the uncertain boundary between natural and cultural meanings in their engagements with fashion and the decorative. The article considers animal fashions and the limits of the human in Djuna Barnes's writing, from early pieces such as 'Vaudeville' (1915) and 'Madame Collects Herself' (1918) to her late poetry, and in her journalism for New York newspapers, Vanity Fair, Charm and elsewhere. It also explores Mina Loy's engagement with decoration and fashion through her poetry, in her essay on 'Modern Poetry' and in her work as a designer and inventor (including her design for a 'Horse Ear Hat'). The article argues that, through motifs of animal decorations in women's fashion, Barnes and Loy imagine animal-human confluences that deconstruct those dualisms and hierarchies that sustain an exploitative anthropocentric economy and a patriarchal cultural elitism.